Disruption of l-Rhamnose Biosynthesis Results in Severe Growth Defects in Streptococcus mutans - Bischer, Andrew P. (J Bacteriol, 2020)
The rhamnose-glucose cell wall polysaccharide (RGP) of Streptococcus mutans plays a significant role in cell division, virulence, and stress protection. Prior studies examined function of the RGP using strains carrying deletions in the machinery involved in RGP assembly. In this study, we explored loss of the substrate for RGP, l-rhamnose, via deletion of rmlD (encoding the protein responsible for the terminal step in l-rhamnose biosynthesis). We demonstrate that loss of rhamnose biosynthesis causes a phenotype similar to strains with disrupted RGP assembly (ΔrgpG and ΔrgpF strains). Deletion of rmlD not only caused a severe growth defect under nonstress growth conditions but also elevated susceptibility of the strain to acid and oxidative stress, common conditions found in the oral cavity. A genetic complement of the ΔrmlD strain completely restored wild-type levels of growth, whereas addition of exogenous rhamnose did not. The loss of rhamnose production also significantly disrupted biofilm formation, an important aspect of S. mutans growth in the oral cavity. Further, we demonstrate that loss of either rmlD or rgpG results in ablation of rhamnose content in the S. mutans cell wall. Taken together, these results highlight the importance of rhamnose production in both the fitness and the ability of S. mutans to overcome environmental stresses. IMPORTANCE Streptococcus mutans is a pathogenic bacterium that is the primary etiologic agent of dental caries, a disease that affects billions yearly. Rhamnose biosynthesis is conserved not only in streptococcal species but in other Gram-positive, as well as Gram-negative, organisms. This study highlights the importance of rhamnose biosynthesis in RGP production for protection of the organism against acid and oxidative stresses, the two major stressors that the organism encounters in the oral cavity. Loss of RGP also severely impacts biofilm formation, the first step in the onset of dental caries. The high conservation of the rhamnose synthesis enzymes, as well as their importance in S. mutans and other organisms, makes them favorable antibiotic targets for the treatment of disease.